2023
DOI: 10.3390/lubricants11050190
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hydrodynamic Lubrication Analysis of Slipper Pair Considering Wear Profile

Abstract: The profile of sealing land is a sensitive factor affecting the thermo-hydrodynamic lubrication characteristics of the slipper pair. In this paper, the non-uniform wear of the running surface under the slipper was presented and defined as the boundary condition. Based on the finite volume method and the successive over-relaxation iteration method, a discrete numerical model coupled with the temperature, pressure, and thickness of the oil film was constructed. The Newton and sequential circulation methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…To sum up, by substituting formulas ( 8)-( 12) into formula (13), the temperature rise because of the relative slide between the slipper and the swash plate is as follows:…”
Section: Oil Film Thickness Model Of Slipper Pairmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, by substituting formulas ( 8)-( 12) into formula (13), the temperature rise because of the relative slide between the slipper and the swash plate is as follows:…”
Section: Oil Film Thickness Model Of Slipper Pairmentioning
confidence: 99%
“…In this process, the outer edge of the slipper is easily subjected to solid contact or collision with the swash plate surface, causing friction and wear on the outer edge of the slipper and destroying the original static pressure support structure. Thus, the overall performance and life of the piston pump are reduced [10][11][12][13][14]. Due to the lack of clear research on the partial wear motion law of the slipper pair of the LDPP, in order to promote the development of the LDPP and improve its overall performance, it is very meaningful to study the motion law of the slipper pair in its actual working condition.…”
Section: Introductionmentioning
confidence: 99%
“…Different rolling forces will affect the operating temperature of bearings, thereby influencing the measurement accuracy of bearing oil film thickness. Some scholars have already measured bearing oil film thickness under thermal expansion conditions and achieved high-precision results [24,25]. However, most detection methods do not account for the influence of temperature on measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the calculation of leakage without considering structural thermal deformation can lead to significant error [9][10][11]. Other researchers also investigated the performance of a mechanical seal considering structural thermal deformation to accurately calculate the leakage rate of the seals in mechanical devices [12][13][14].…”
Section: Introductionmentioning
confidence: 99%